2010
DOI: 10.1017/s0017089510000674
|View full text |Cite
|
Sign up to set email alerts
|

GEOMETRIC INVARIANT THEORY FOR HOLOMORPHIC FOLIATIONS ON ℂℙ2 OF DEGREE 2

Abstract: Abstract. Let F 2 be the space of the holomorphic foliations on ‫ސރ‬ 2 of degree 2. In this paper we study the linear action PGL(3, ‫)ރ‬ × F 2 → F 2 given by gX = DgX • (g −1 ) in the sense of the Geometric Invariant Theory. We obtain a characterisation of unstable and stable foliations according to properties of singular points and existence of invariant lines. We also prove that if X is an unstable foliation of degree 2, then X is transversal with respect to a rational fibration. Finally we prove that the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the first one we characterize the foliations with isolated singularities in the unique open stratum S 0 , which is the set of semistable foliations. In the second one we characterize the semistable foliations of degree 1, the proof of this can be found in Alcántara (2011).…”
Section: Lemma 32 S J Is Irreducible and It Is Open In Itsmentioning
confidence: 99%
“…In the first one we characterize the foliations with isolated singularities in the unique open stratum S 0 , which is the set of semistable foliations. In the second one we characterize the semistable foliations of degree 1, the proof of this can be found in Alcántara (2011).…”
Section: Lemma 32 S J Is Irreducible and It Is Open In Itsmentioning
confidence: 99%
“…It was using this criterion that Goméz-Mont and Kempf [8] have shown that a foliation whose all singular points have Milnor number 1 is stable, that is, corresponds to a stable point of F m . And Alcántara [1], [2] has characterized the semi-stable foliations of degrees 1 and 2.…”
Section: The Actionmentioning
confidence: 99%
“…(In fact, they showed the same result holds for singular foliations of higher dimension spaces as well.) Only recently, Alcántara [1], [2] has characterized the semi-stable foliations of degree 1 and 2, and studied their quotient spaces.…”
Section: Introductionmentioning
confidence: 99%